A phthalimide-based fluorescent probe for thiophenol detection in water samples and living cells with a large Stokes shift. Issue 43 (28th October 2015) - Liu, Xingjiang; Yang, Liu; Gao, Li; Chen, Wenqiang; Qi, Fengpei; Song, Xiangzhi
Abstract: A phthalimide-based fluorescent probe for the detection of thiophenol was developed based on the combination of photo-induced electron transfer (PET) and excited-state intramolecular proton transfer (ESIPT) mechanisms. This probe displays high sensitivity and good selectivity toward thiophenol with a large Stokes shift (161 nm) and a low detection limit (3.5 nM, based on S/N=3). Furthermore, the applications of this probe for quantitative detection of thiophenol in real water samples and imaging intracellular thiophenol in living cells were successfully demonstrated. Graphical abstract: